PERBANDINGAN TINGKAT KESEHATAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH GO PUBLIC PADA PT. SAT NUSAPERSADA TBK. BATAM - Syahril Amzah; Hamidi H (EQUILIBIRIA, 2014)
Batam’s Economic indicator year 2005-2011 shows graduate increasing every year 13, 5 US $ billion in average. Since FTZ has implemented in Batam, resulted tight manufacture and trade competition. In order to compensate it, especially in globalization and information technologies, manufacture needs kind of support from the public as well as government, by go public.The research is to research whether any significance gap in term of manufacture financial performance before and after go public. Manufacture financial performance is measured by four aspects of ratio: liquidity, solvability, rent ability (ROE) and rent ability (ROA). Those will be compared before and after go public to see whether any increasing, similar or even decrease.PT. Sat Nusapersada Tbk. Batam as an object in this research. This research is using historical data source. The seconder data has been collected from the market stock exchange prospectus and manufacture financial report start from five years before and after go public. Financial Performance shows it’s difference before and after go public by two kind of measurements: KepMen BUMN Nomor : KEP-100/MBU/2002  date: 4th June 2002  and statistical difference test.KepMen BUMN Nomor : KEP-100/MBU/2002  date: 4th June 2002  and statistical difference test show that there are difference of significant financial performance after go public. Showed at the solvability and rentability ratio. Solvability 174%, rentability (ROE) 6,1% and rentability (ROA) 1,38% before go public. While, Solvability 423%, rentability (Return of Equity) -2,48% and rentability (Return of Assets) -1,33%.